Evaluating the correlation between adrenal gland dimensions and aortic diameter in healthy dogs. (21st April 2019) - Ghavidel, Mahshid; Mirshahi, Ali; Azizzadeh, Mohammad; Khoshnegah, Javad
Abstract: In the present study, the relationship of normal adrenal dimensions with weight, aortic diameter, age and sex was evaluated. Moreover, a formula for estimating the normal dimensions of adrenal gland was provided. Thirty‐two intact adult dogs that were considered healthy based on history, physical examination, routine blood works and specific adrenal tests as well as absence of any abnormal ultrasonographic findings were included. Adrenal glands and abdominal aorta were imaged in the sagittal plane by ultrasound. Length, maximal height of the cranial and caudal poles, area and circumference of the left and right adrenal glands and also the internal diameter of the abdominal aorta were measured. Analysis showed that there is a positive correlation between the adrenal gland dimensions and weight and aortic diameter. The ratio of adrenal gland dimensions and the aortic diameter was calculated, but this ratio showed a great amount of variability in tandem with a significant correlation to the weight; Meaning that the ratio of the adrenal gland dimensions to the aortic diameter was not a reliable index for evaluating the size of the normal adrenal gland in animals with different weights. Therefore, we used the weight along with adrenal measurements in a linear regression model, and then, we were able to estimate the adrenal gland dimensions in different weights. Knowing the relationship of normal adrenal dimensions with the indices such as weight, age, sex and diameter of abdominal aorta can help the clinicians to diagnose the adrenal gland diseases.